Favorable Cardiovascular Health Is Associated With Lower Hepatocyte Growth Factor Levels in the Multi-Ethnic Study of Atherosclerosis - Osibogun, Olatokunbo; Ogunmoroti, Oluseye; Ferraro, Richard A.; Ndumele, Chiadi E.; Burke, Gregory L.; Larson, Nicholas B.; Bielinski, Suzette J.; Michos, Erin D. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Hepatocyte growth factor (HGF) is a cytokine released in response to endothelial injury and a potential biomarker of cardiovascular disease (CVD) risk. We examined the association between cardiovascular health (CVH) and HGF in a multi-ethnic cohort of adults free from CVD at baseline. Methods: This cross-sectional study conducted between 2020-2021 used MESA baseline examination data (2000-2002) from 6,490 US adults aged 45-84 years. The independent variable was CVH measured by the CVH score and number of ideal metrics. The score was derived from seven metrics: smoking, body mass index, physical activity, diet, total cholesterol, blood pressure and blood glucose. Each metric was scored 0 points (poor), 1 point (intermediate) and 2 points (ideal). The total CVH score ranged from 0-14. An inadequate score was 0-8, average, 9-10 and optimal, 11-14. The dependent variable was logarithmically-transformed HGF. We used regression analyses to estimate associations between CVH and HGF adjusting for sociodemographic factors. Results: Participants’ mean (SD) age was 62 (10) years. Fifty-three percent were female. A one-unit increment in the CVH score was significantly associated with 3% lower HGF levels. Average and optimal CVH scores were significantly associated with 8% and 12% lower HGF levels, respectively, compared to inadequate scores. Additionally, a greater number of ideal metrics was associated with lower HGF levels. Conclusion: Favorable CVH was significantly associated with lower HGF levels in this ethnically diverse cohort. Interventions aimed at promoting and preserving favorable CVH may reduce the risk of endothelial injury as indicated by lower serum HGF levels.